The Function of the Family in Character Building in the Age of Digitization - Khoirina, Cony (Universitas Muhammadiyah Surakarta, 2022)
The family is a factor in shaping the child's personality and the main character building. In this case, parents play a very important role, teaching character education from an early age so that individuals or children behave in accordance with applicable norms. Creating an effective two-way communication discussion between parents and children so as to form a harmonious relationship. Besides the need embed values religious in this digital era in order to become a pedestal in behavior. The purpose of this study is to describe the function of the family in formation character diera digitization . The writing of this research uses the method of library research or library research . In this study, references were collected from journal articles, books, and facts related to the function of the family in character building in the digitalization era.